What's Love Got to Do with it? An Ecofeminist Approach to Inter-Animal and Intra-Cultural Conflicts of Interest - Emmerman, Karen S. (2019)
Many familial and cultural traditions rely on animals for their fulfillment - think of Christmas ham, Rosh Hashannah chicken soup, Fourth of July barbeques, and so forth. Though philosophers writing in animal ethics often dismiss interests in certain foods as trivial, these food-based traditions pose a significant moral problem for those who take animals' lives and interests seriously. One must either turn one's back on one's community or on the animals. In this paper, I consider the under-theorized area of intra-cultural critique. My focus is how we should think about and seek to resolve inter-animal conflicts of interest that arise within our own communities and cultural or religious groups. How should a theory that takes animals seriously approach a conflict between animals' interests and culturally important human interests in the context of one's own cultural, ethnic, or religious group? How, for example, should we think about the person staring down at a bowl of her grandmother's chicken soup while recognizing the moral impermissibility of slaughtering chickens for human consumption? In contrast to traditional approaches that fail to take these robust, food-based, interests into account, I offer an ecofeminist approach that highlights the importance of respecting animals' interests while also undertaking the work of moral repair to address damage done to relationships of love and care in the process.
Keywords: Animals; Basic interests; conflicts of interest; Ecofeminism; Foodways; Jewish vegetarianism; moral repair; Nonbasic interests; Veganism; Culture; Gender; intersectional veganism